Analisis dan Perancangan Sistem Pengelola Data Menuju Implementasi Data Warehouse Untuk Mendukung Administrasi E-Procurement - Pradhana, I Gusti Ngurah Adhy; Giriantari, I.A.D; Sudarma, Made (Majalah Ilmiah Teknologi Elektro; Vol 17 No 2 (2018): (May - Agustus) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2018.v17i02.P12, 2018)
Abstract — ULP (Procurement Unit) Udayana University is an institution that organizes the procurement process of Goods/ Services within Udayana University, that includes procurement planning, procurement implementation and reporting of the procurement. This study resulted in a data warehouse application that can summarize, integrate historical data and present information from various dimensions that assist stakeholders in analyzing their policy strategies. Information generated from data warehouse will make it easy for reporting of Goods/Services Procurement at Udayana University to summarize the data and also enable stakeholders to view their data from various dimensions. Data warehouse is designed to facilitate the organization in obtaining information for further analysis and can also be a reference in developing other applications. Data warehouse modeling that has built names SIGAP, which has proven to successfully improve the performance of government goods procurement information system in Udayana University. The improvement is the speed and accurity in finding procurement report for stakeholders or other user. This is measured from the feasibility test of the system which showed in satisfaction score for efficiency is 4.31 out of 5.00. This shows that stakeholders or user can get procurement reports faster using SIGAP application than usual method.